Exploring children's condition of adolescent mothers in East Kalimantan Indonesia: an ethnography study - Wahyuni, Tri; Rungreangkulkij, Somporn (Universitas Airlangga, 2023)
Introduction: It has been revealed several times that children born to adolescent mothers tend to experience problems in health, growth, and development, also social problems, which continued until now and have even tended to get worse due to various factors such as a pandemic, deteriorating economic conditions, and decreased sense of care among human beings. It is associated with the unpreparedness of adolescent mothers to face the dual roles carry out as mothers and as adolescents themselves. The study aims to explore and describe children's condition of adolescent mothers during their motherhood in the community Methods: This is an ethnography study, collected data by observation, in-depth interviews, and field notes to explore behaviors, beliefs, values, and perceptions of adolescent mothers about children's health status. The main key informants were 20 participants, the data were analyzed with content analysis. Results: The result revealed 3 children's conditions of adolescent mothers in the community which involve: 1) Children's health status, 2) Children's breastfeeding status, and 3) Children's immunization status. Conclusion: Many of their children have health problems at birth and at this time, and it was related to health problems during pregnancy. The low coverage of exclusive breastfeeding and basic immunization is caused by low support from families, inconsistent cultures with beliefs, incomplete information, and the conditions of the Covid-19 pandemic. Stigmatize as adolescent mothers cause they lack carry out regular check-ups on their children.